Childhood Respiratory Outpatient Visits Correlate With Socioeconomic Status and Drive Geographic Patterns in Antibiotic Prescribing. (27th April 2021) - Kissler, Stephen M; Klevens, R Monina; Barnett, Michael L; Grad, Yonatan H
Abstract: Background: Reducing geographic disparities in antibiotic prescribing is a central public health priority to combat antibiotic resistance, but drivers of this variation have been unclear. Methods: We measured how variation in outpatient visit rates (observed disease) and antibiotic prescribing rates per visit (prescribing practices) contributed to geographic variation in per capita antibiotic prescribing in Massachusetts residents younger than 65 years between 2011 and 2015. Results: Of the difference in per capita antibiotic prescribing between high- and low-prescribing census tracts in Massachusetts, 45.2% was attributable to variation in outpatient visit rates, while 25.8% was explained by prescribing practices. Outpatient visits for sinusitis, pharyngitis, and suppurative otitis media accounted for 30.3% of the gap in prescribing, with most of the variation in visit rates concentrated in children younger than 10 years. Outpatient visits for these conditions were less frequent in census tracts with high social deprivation index. Conclusions: Interventions aimed at reducing geographic disparities in antibiotic prescribing should target the drivers of outpatient visits for respiratory illness and should account for possible underutilization of health services in areas with the lowest antibiotic consumption. Our findings challenge the conventional wisdom that prescribing practices are the main driver of geographic disparities in antibiotic use. Abstract : Variation in per capita antibiotic prescribing between high- and low-prescribing census tracts in Massachusetts was mainly attributable to variation in outpatient visits for pediatric respiratory conditions, with less frequent visits in census tracts with high social deprivation index.